Uji Daya Hambat Ekstrak Daun Sirih Hijau (Piper betle L.), Daun Sirih Merah (Piper crocatum Ruiz & Pav.), dan Daun Sirih Hutan (Piper aduncum L.) Terhadap Pertumbuhan Candida albicans - Zuraidah Zuraidah; Adi Gunawan; Elita Agustina (Universitas Hasanuddin, 2021)
Betel leaf (Piperaceae) has antiseptic and anti-fungal properties that have long been recognized by the public. Betel leaf extract has been widely reported as an anti-fungal agent such as the Candida albican fungus. The fungus Candida albicans is a normal flora of the human body that causes candidiasis. This study used extracts of three types of betel leaf, namely green betel leaf (Piper betle L.), red betel leaf (Piper crocatum Ruiz & Pav), and forest betel leaf (Piper aduncum L.) to inhibit the growth of the Candida albicans. in vitro. The research objective was to determine the effect of giving betel leaf extract on the growth of the Candida albicans. This study used the disc diffusion method and completely randomized design (CRD) with five treatments and four repetitions. Collecting data by measuring the clear zone formed in each treatment. Average measurement results for red betel = 28.7, forest betel = 13.00, red betel = 15.46, K + = 34.92, and K- = 0. The results of the Duncan Distance Difference Test showed that each treatment had a very significant effect in inhibiting the growth of the Candida albicans. Thus it is proven that the betel leaf extract (Piper sp.) Affects the growth of the Candida albicans.